Selective hydrogenation of levulinic acid to γ-valerolactone using in situ generated ruthenium nanoparticles derived from Ru–NHC complexes. Issue 8 (25th January 2016) - Tay, Boon Ying; Wang, Cun; Phua, Pim Huat; Stubbs, Ludger Paul; Huynh, Han Vinh
Abstract : Ruthenium(ii ) NHC complexes give rise to highly active and selective ruthenium nanoparticles for the conversion of levulinic acid to γ-valerolactone in water. Abstract : Hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL) was studied by using mono- and bidentate p -cymene ruthenium(ii ) N-heterocyclic carbene (NHC) complexes as catalyst precursors. In water, all complexes were found to be reduced in situ to form ruthenium nanoparticles (RuNPs) with a high hydrogenation activity. In organic solvents, complexes with monodentate NHC ligands also formed nanoparticles, while complexes with bidentate ligands gave rise to stable homogeneous catalysts with moderate hydrogenation activities.